Perceptions of PEP grant influences on CSPAP implementation - Berei, Catherine P.; Karp, Grace Goc; Olsen, Simon; Fennell, Marcis; Drake, Elisa (Research Quarterly for Exercise and Sport, 2017)
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Stakeholders’ perspectives on the effects of a PEP grant on a district-wide CSPAP - Abel-Berei, Catherine P.; Karp, Grace Goc; Fennell, Marcis; Drake, Elisa M.; Olsen, Simon (Journal of Teaching in Physical Education, 2021)
A Comprehensive School Physical Activity Program (CSPAP) can help children be physically active for 60 min/day. Physical Education for Progress grants provided opportunities to improve physical education and physical activity programming. Purpose: This study explored stakeholders' perspectives on the effects of a Physical Education for Progress grant on a district-wide CSPAP. Method: Stakeholders included physical educators (n = 10; K-12), administrators (n = 6), and one superintendent. Individual, semistructured interviews were used to examine how the grant affected stakeholders' perspectives of the CSPAP. Results: The grant affected the CSPAP by providing (a) opportunities for professional development, (b) opportunities to establish a K-12 curriculum map, and (c) access to equipment and resources. Discussion: Framed in social ecological theory, intrapersonal, interpersonal, institutional, and community levels were influenced by the grant. Interactions between levels enabled changes in all CSPAP components, especially quality PE. Conclusion: A Physical Education for Progress grant is a successful mechanism to enhance a district-wide CSPAP. © 2021 Human Kinetics, Inc.
Keywords: dept.hms; peer-reviewed

The Situation With Modern Leadership Stacking: Racial Politics, Racial Discourse, and the Realities for Black American Coaches—Who Keeps Moving the Goalposts? - Harrison, C.; Mebane, Karreem; Fennell, Marcis; Griffin, Whitney; McAllister, Dre; Hart, Richard; McArdle, Danielle (Kinesiology Review, 2025)
Keywords: Black male; Gender studies; Law; NFL hiring practices; Political science; Politics; Psychology; Race (biology); Racial bias; Rooney Rule; Social psychology; Sociology; coaching pipeline; dept.rec; peer-reviewed; racial stacking